Etude bibliographique sur l’activitéantibactérienne des nanoparticules de ZnO - كوثر, علال; اسمهان, دقة; هاجر, بن قدور (University of El-Oued, 2021)
"n this work, we presented a protocol for the green synthesis of ZnO nanoparticles from Phoenix Dactylifera leaves, followed by a literature review on the bacterial activity against pathogenic bacteria such as E. coli, S. aureus, B. subtilis, P. aeruginosa and S. paratyphi, by using ZnO nanoparticles. The inhibition zones clearly show that the bio-synthesized ZnO nanoparticles disrupt the cellular membrane with high rates of surface oxygen species generation and ultimately cause pathogen death. The green synthesis provides low cost and environmentally friendly ZnO nanoparticles. At the same time, ZnO nanoparticles have shown greater efficacy in inhibiting the growth of bacteria.""عرضنا في هذا العمل ،بروتوكول لتحضير جسيمات النانوية لأكسيد الزنك بطريقة التوليف الأخضر باستعمال أوراق Phoenix Dactylifera ،بعد ذلك اجرينا دراسة نظرية حولا لنشاط البكتيري لجسيمات أكسيد الزنك ZnO مثل Coli .EوAureus .S و subtilis .B وaeruginosa .P و Paratyphi .S . تظهر مناطق التثبيط بوضوح أن الجسيمات النانوية ZnO المركبة حيويا تعطلا لغشاء الخلوي بمعدلات عالية من نسبة الأكسجين السطحيات سبب في النهاية لموت العامل الممرض. يوفر التوليف الأخضر تكلفة منخفضة وجسيمات ZnO النانوية صديقة للبيئة. في الوقت نفسه ، اظهرت جسيمات ZnO النانوية كفاءة عالية فيتثبط نمو البكتيريا"
Génie chimiqueمذكرة ماستر تخصص
Keywords: "Nanoparticles;ZnO;antibacterialactivity;biosynthesis; plants. "; الجسيمات النانوية،النشاط البكتيري،التوليف الأخضر، النباتات.